CONSTRUCTION AND OPTIMIZATION OF STRUCTURE-BASED VIRTUAL SCREENING PROTOCOLS TO IDENTIFY CYCLOOXYGENASE-1 INHIBITORS USING OPEN BABEL, SPORES AND PLANTS - Enade Perdana Istyastono (Indonesian Journal of Chemistry, 2012)
Structure-Based Virtual Screening (SBVS) protocols to identify cyclooxygenase-1 (COX-1) inhibitors have been constructed and optimized based on their Root Mean Square Deviation (RMSD) values of the docked pose and the crystal structure pose of the reference ligand. Employing a COX-1 structure obtained from the Protein Data Bank (pdb) with code 2OYE as the reference protein and PLANTS1.2 as the molecular docking simulation program, the SBVS protocols were mainly built. The preparation steps involved SPORES and Open Babel, while the results analysis involved PyMOL to calculate the RMSD and R computational statistics software to perform the statistics calculations. The results show that these construction and optimization processes could provide an SBVS protocol to identify COX-1 inhibitors that is accurately able to redock the reference ligand with the RMSD value of 0.633 Å.